Fabrication and testing of a multi-reflector type solar oven - BEENA THOMAS HELEN ALEX JAYARAJAN R RAJEEV M; Dr. Jobi V. Paul (Guide) (Tavanur 1992 Department of Agricultural Processing and Structure)
Fabrication and testing of a multi-reflector type solar oven
Fabrication and testing of a multi-reflector type solar oven